Near-Infrared Optical Imaging of Integrin αβ in Human Tumor Xenografts - Wei Wang; Shi Ke; Qingping Wu; Chusilp Charnsangavej; Mikhail Gurfinkel; Juri G. Gelovani; James L. Abbruzzese; Eva M. Sevick-Muraca; Chun Li (Molecular Imaging)
In vivo optical imaging is potentially useful for evaluating the presence of tumor markers that are targets of molecular medicine. Here we report the synthesis and characterization of integrin αvβ3-targeted peptide cyclo(Lys–Arg–Gly–Asp–Phe) [c(KRGDf)] labeled with fluorescence dyes with wavelength spanning from the visible/near infrared (Cy5.5) to the true near infrared (IRDye800) for optical imaging. In vitro, the peptide–dye conjugates bound specifically to tumor cells expressing αvβ3. When administered intravenously into mice at a dose of 6 nmol/mouse, the conjugates accumulated in tumors expressing αvβ3. The tumor-to-background ratios for human KS1767 Kaposi's sarcoma in mice injected with Cy5.5–c(KRGDf) and Cy5.5 were 5.5 and 1.5, respectively. Preinjection of c(KRGDf) blocked the uptake of Cy5.5–c(KRGDf) in tumors by 89%. In αvβ3-positive M21 and αvβ3-negative M21-L human melanoma, fluorescence intensity in the tumor of mice injected with IRDye800–c(KRGDf) was 2.3 and 1.3 times that in normal tissue, respectively. Dynamic imaging revealed that Cy5.5–c(KRGDf) was rapidly taken up by KS1767 tumor immediately after bolus injection. The rate of its uptake in the tumor was reduced by preinjection of c(KRGDf) in an interval time-dependent manner. Our data suggest that near-infrared fluorescence imaging may be applied to the detection of tumors expressing integrin αvβ3 and to the assessment of the optimal biological dose and schedule of targeted therapies.